2019
DOI: 10.1037/xhp0000612
|View full text |Cite
|
Sign up to set email alerts
|

Intentional binding is unrelated to action intention.

Abstract: The present study examined the role of voluntary motor commands in the subjective temporal attraction between an action and its sensory consequence termed as intentional binding. Participants either pressed a key voluntarily or involuntarily while seeing a rotating clock hand. The key press was followed by a short beep tone in some blocks of trials. Then, the position of the clock hand at action or tone occurrence was judged. Trials in which key presses and tones occurred separately provided baseline measures.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

11
63
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 57 publications
(78 citation statements)
references
References 24 publications
11
63
0
Order By: Relevance
“…Additionally, there were no differences at all between the ownership ratings for different conditions. These results add to previous studies which showed diverging patterns of results for explicit and implicit measures of agency (such as temporal binding; Buehner, 2012; Kirsch, Kunde, & Herbort, 2019;Majchrowicz & Wierzchoń, 2018;Moore, Lagnado, Deal, & Haggard, 2009;Schwarz, Weller, Klaffehn, & Pfister, 2019;Suzuki, Lush, Seth, & Roseboom, 2019) and extend these findings to the spatial domain and measures of ownership as well.…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…Additionally, there were no differences at all between the ownership ratings for different conditions. These results add to previous studies which showed diverging patterns of results for explicit and implicit measures of agency (such as temporal binding; Buehner, 2012; Kirsch, Kunde, & Herbort, 2019;Majchrowicz & Wierzchoń, 2018;Moore, Lagnado, Deal, & Haggard, 2009;Schwarz, Weller, Klaffehn, & Pfister, 2019;Suzuki, Lush, Seth, & Roseboom, 2019) and extend these findings to the spatial domain and measures of ownership as well.…”
Section: Discussionsupporting
confidence: 84%
“…However, and especially against this background, the inconsistencies between the implicit binding measure and the explicit ratings are an interesting finding that add up to an increasing number of studies showing that implicit measures of agency and ownership, such as temporal or spatial binding, might be related to explicit sense of agency and ownership to a lesser extent than previously thought (Buehner, 2012 ; Kirsch et al, 2019 ; Majchrowicz & Wierzchoń, 2018 ; Moore et al, 2009 ; Schwarz et al, 2019 ; Suzuki et al, 2019 ). While we cannot rule out possible methodological reasons for our inconsistent findings, disentangling the relationship between explicit agency and ownership experiences and different binding measures further could be an interesting question for future research.…”
Section: Discussionmentioning
confidence: 96%
“…Beyond the fact that temporal binding is sensitive to intentions and is thus often referred to as intentional binding (e.g., Haggard & Tsakiris, 2009;Moore & Obhi, 2012), it has been shown that temporal binding is also informed by causality, which is why intentions are not a prerequisite for it to arise (Buehner, 2012;Suzuki, Lush, Seth, & Roseboom, 2019). It is a widely employed measure for time estimations in both healthy participants and clinical populations such as patients with schizophrenia or Parkinson's disease (Buehner & Humphreys, 2009;Haggard, Martin, Taylor-Clarke, Jeannerod, & Franck, 2003;Kirsch, Kunde, & Herbort, 2019;Moore et al, 2010). Despite the common use of temporal binding as a measure, as of yet there are not many ways of studying it.…”
Section: Introductionmentioning
confidence: 99%
“…If causality perception indeed decreases with more action steps, an implicit measure of SoA should also reflect this. In fact, both sensory attenuation and intentional binding have been questioned regarding their ability to adequately capture the SoA, because they have also been observed outside the context of voluntary actions (Kaiser & Schütz-Bosbach, 2018;Kirsch et al, 2019;Suzuki et al, 2019). Thus, in line with some arguments outlined above, the present sensory attenuation effects may be a consequence of better temporal predictability of the tone in the three-step action, rather than reflecting a stronger SoA.…”
Section: Discussionmentioning
confidence: 72%